Sign Here! Handwriting in the Age of New Media - Neef, Sonja; Ketelaar, Eric; van Dijck, José (Transformations in Art and Culture, 2006)
Sign Here! Handwriting in the Age of New Media features a number of articles from different fields, reaching from cultural and media studies to literature, film and art, and from philosophy and information studies to law and archival studies. Questions addressed in this book are: Will handwriting disappear in the age of new (digital) media? What happens to important cultural and legal concepts, such as original, copy, authenticity, reproducibility, uniqueness, and iterability? Where is the writing hand to be located if handwriting is performed not immediately 'by hand' but when it is (re)mediated by electronic or artistic media? Sign Here! Handwriting in the Age of New Media is the first part in the series Transformations in Art and Culture.